2010
DOI: 10.1128/aem.00698-09
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Synthesized Gene Encoding Cationic Peptide Cecropin B in Transgenic Tomato Plants Protects against Bacterial Diseases

Abstract: The cationic lytic peptide cecropin B (CB), isolated from the giant silk moth (Hyalophora cecropia), has been shown to effectively eliminate Gram-negative and some Gram-positive bacteria. In this study, the effects of chemically synthesized CB on plant pathogens were investigated. The S 50 s (the peptide concentrations causing 50% survival of a pathogenic bacterium) of CB against two major pathogens of the tomato, Ralstonia solanacearum and Xanthomonas campestris pv. vesicatoria, were 529.6 g/ml and 0.29 g/ml,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 46 publications
0
44
0
3
Order By: Relevance
“…In the present study, transgenic tobacco plants expressing the Lfc gene were developed to enhance resistance against a broad spectrum of plant pathogens. As a result, Lfc exhibited bactericidal activity as high as bactericidal peptides, such as sarcotoxin IA derived from fresh y Sarcophaga peregrina (Ohshima et al 1999) and cecropin derived from giant silk moth Hylophora cecropiaie (Hightower et al 1994;Jan et al 2010;Jaynes et al 1993).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, transgenic tobacco plants expressing the Lfc gene were developed to enhance resistance against a broad spectrum of plant pathogens. As a result, Lfc exhibited bactericidal activity as high as bactericidal peptides, such as sarcotoxin IA derived from fresh y Sarcophaga peregrina (Ohshima et al 1999) and cecropin derived from giant silk moth Hylophora cecropiaie (Hightower et al 1994;Jan et al 2010;Jaynes et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic plants showed considerably greater resistance to pathogens (Hightower et al 1994;Jan et al 2010;Jaynes et al 1993;Ohshima et al 1999;Osusky et al 2000;Osusky et al 2004) and parasitic weeds (Radi et al 2006) than to the wild types. Zhang et al (1998) reported that transgenic tobacco expressing human lactoferrin protein demonstrated signi cant delays in developing bacterial wilt symptoms when inoculated with the bacterial pathogen Ralstonia solanacearum.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The secretion of foreign AMPs to apoplast might enhance the peptide-pathogen interaction [68,69], but the respective peptide might be exposed to plant endogenous proteases and be degraded and/or negatively affect the fitness and fertility of transgenic plants [70]. Conversely, several studies have indicated that targeting to the apoplastic space is not always necessary to obtain disease resistance [71].…”
Section: Peptide Purification and Antimicrobial Activity Evaluationmentioning
confidence: 99%
“…Antimicrobial peptides, which are expressed from only a single heterologous gene, provide a solution for a broad-spectrum ranging from anti-bacteria, -fungi and -protozoan (Farrokhi et al, 2008;Rahnamaeian and Vilcinskas, 2012). These peptides have been successfully integrated and transformed into the nuclei and chloroplasts of higher plants (DeGray et al, 2001, Jan et al, 2010. To prevent the prey from invertebrates, several allelochemicals from cyanobacteria can be introduced and expressed to defend against potential predators and grazers (Berry et al, 2008;Rastogi and Sinha, 2009).…”
Section: Crop Protectionmentioning
confidence: 99%